Lysophosphatidic acid 2 alleviates deep vein thrombosis via protective endothelial barrier function - Bai Ruifeng; Yue Xinyang; Tian Xuan; Zhao Huiru; Liu Ying; Li Tian; Wu Jun (Open Medicine)
The specific role of lysophosphatidic acid 2 (LPA2) in deep vein thrombosis (DVT) remains unclear.